Repair and regeneration of the pronephric kidney in Xenopus laevis tadpoles. - Caine, Shoshoni. (2017)
Abstract: The kidney is a unique organ in that it develops through three distinct forms of increasing complexity, with the most embryonic form (pronephros) serving as the functional organ in the tadpoles of the amphibian model system, Xenopus laevis, and the most complex form (metanephros) being found in adult humans. Since the developmental programs that govern organogenesis in all three kidneys are conserved, and all kidneys share the same structural units and basic functions, we can utilize these simpler pronephric kidneys to investigate the repair mechanisms in induced renal damage. To accomplish this, we developed a novel pronephrectomy technique to excise specific parts of the kidney in X. laevis tadpoles, and examined the repair responses that followed. The results of these studies demonstrate for the first time that an amphibian pronephros is able to regenerate lost structures. We also begin to elucidate the mechanisms through which this regenerative phenomenon occurs, and have revealed dualistic roles for the extracellular matrix remodeler, Matrix metalloproteinase-9. This protease is expressed during two distinct windows of pronephric regeneration: immediately after injury, and again five days later. While the early expression of XMMP-9 promotes pronephric regeneration, proteolytic activity of this enzyme during the second phase appears to inhibit this regenerative process. In this dissertation, we propose likely mechanisms for these disparate roles of XMMP-9.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Biology.; Advisor: Kelly McLaughlin.; Committee: Harry Bernheim, Juliet Fuhrman, Michael Levin, Mitch McVey, and Iain Drummond.; Keywords: Biology, and Developmental biology.